Computer science students' use of the internet for academic purposes: difficulties and learning processes. Issue 3 (3rd July 2018) - Ben-David Kolikant, Yifat; ma'ayan, Ze'ev
ABSTRACT: Higher-education students now have more alternatives for searching for information than previous generations had. The Internet is a vast ocean of information sources, albeit with diverse reliability and quality. In Web 2.0 platforms, any participant can be a content creator. This reality is challenging for both the instructors and the students. We conducted interviews with 12 Computer Science students and 8 instructors from two universities to (a) identify the difficulties students encounter, if at all, (b) identify the learning processes that students undergo, if at all, when using the Internet for their CS studies, in particular, programming tasks; and (c) elicit instructors' perceptions of students' use of the Internet. Both students and instructors agreed that although using the Internet is not trivial, direct teaching of this skill is unnecessary. Instructors differed in their attitudes towards students' use of the internet. We found that in the first year the students' use of the Internet and their difficulties are similar to reports in the empirical literature, and echo the instructors' concerns. However, after extensive experience, students undergo a learning process, and their ability to navigate the myriad sources, as well as to search, manage, and effectively evaluate Internet sources improves. Students mentioned their improved abilities to code as a means to effectively evaluate information sources.